2004
DOI: 10.1002/chin.200412237
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Techniques in Organic Synthesis

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Continuous‐flow systems have attracted considerable attention as a novel tool for catalytic organic synthesis, and enable to improve the reusability of the catalyst. Compared with traditional batch systems, the continuous‐flow systems provide some advantages, such as high operability, easy control of the reaction, automation, miniaturization, and scale up.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous‐flow systems have attracted considerable attention as a novel tool for catalytic organic synthesis, and enable to improve the reusability of the catalyst. Compared with traditional batch systems, the continuous‐flow systems provide some advantages, such as high operability, easy control of the reaction, automation, miniaturization, and scale up.…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial prototyping strategies have also allowed preparation of large libraries in single batch reactions [10]. Improvements to synthesizers, including continuous-flow and microwave-assisted techniques, have allowed ultra-rapid fabrication for high-throughput prototyping synthesis [11][12][13][14][15][16]. While these new tools have proven effective, they require expensive equipment or specialized fabrication tools.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the flow mode generally allows lowering the E-factor of a production process, by maintaining the catalyst active over large duration, by minimizing unproductive sequences and by reducing the waste/products ratio [16]. To design a truly green and industrially practicable process, the conversion of a batch process to a continuous flow process is often an essential step [17]. In the context of biocatalytic transamination, Andrade et al demonstrated the flow production of chiral amines using immobilized mutants of E. coli-designed to overexpress the desired transaminase [18].…”
Section: Introductionmentioning
confidence: 99%